2020
DOI: 10.3390/antiox9111164
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic and Methylxanthine Bioaccessibility of Cocoa Bean Shell Functional Biscuits: Metabolomics Approach and Intestinal Permeability through Caco-2 Cell Models

Abstract: Cocoa bean shell (CBS), a by-product with considerable concentrations of bioactive compounds and proven biofunctional potential, has been demonstrated to be a suitable ingredient for high-fiber functional biscuits adapted to diabetic consumers. In this work, the in vitro bioaccessibility and intestinal absorption of polyphenols and methylxanthines contained in these biscuits were evaluated, and the effect of the food matrix was studied. Biscuits containing CBS and the CBS alone underwent in vitro digestion fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…The beneficial property of CBS in preserving intestinal cell layer from permeability alteration, suggested by the above data, could be due to the high concentration of antioxidant polyphenols which are present in this byproduct [ 33 ] and that have been recently emerged for their potential modulatory properties with respect to intestinal permeability [ 18 ]. (-)-Epicatechin was shown to prevent intestinal barrier permeabilization and inflammation both in vitro in TNFα-treated CaCo-2 cell monolayers and in vivo in male C57BL/6J mice fed with a high-fat diet through a negative modulation of NADPH oxidase, reactive oxygen species production, and NF-κB activation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The beneficial property of CBS in preserving intestinal cell layer from permeability alteration, suggested by the above data, could be due to the high concentration of antioxidant polyphenols which are present in this byproduct [ 33 ] and that have been recently emerged for their potential modulatory properties with respect to intestinal permeability [ 18 ]. (-)-Epicatechin was shown to prevent intestinal barrier permeabilization and inflammation both in vitro in TNFα-treated CaCo-2 cell monolayers and in vivo in male C57BL/6J mice fed with a high-fat diet through a negative modulation of NADPH oxidase, reactive oxygen species production, and NF-κB activation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported data underline the ability of CBS and CBS-enriched ice cream in preserving the intestinal cell monolayer from the deranging action of an oxysterol mixture detectable in cholesterol rich foods in terms of reduced inflammation, TJ protein loss, and redistribution, as well as stress-related antioxidant response potentiation. Various studies have suggested cocoa bean shell reuse in functional food because of its richness in polyphenols’ potential benefit on health [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water acidified with 0.1 % formic acid (solvent A) and methanol acidified with 0.1 % formic acid (solvent B) served as the mobile phases. The separation method and ESI-QTOF set-tings for data acquisition (positive mode) were performed as described previously [40]. Data acquisition and analysis were carried out using the B.04 SP3 version of the MassHunter Acquisition software for QTOF and the B.08 version of MassHunter Qualitative Analysis software (Agilent Technologies), respectively.…”
Section: Lc-hrms and Metabolomic Studymentioning
confidence: 99%